Áreas verdes ocupadas: realocação dos moradores ou urbanização? estudo de caso no município de Votorantim-SP - Savella, Elzo (2013)
Open spaces for public use, the green spaces include squares, public gardens, urban parks and areas with woody vegetation. In this work the object of study are the woody vegetation areas intended for environmental and recreational purposes. In the municipality of Votorantim/SP there are 133 spaces that fit in this concept, while 20 were occupied by people looking for housing space. As a result some questions arise. The first is about the appropriate use of these spaces. The second is how to solve the problem of precarious housing in these areas: residents should be relocated and the areas should be recovered, or the residents should remain in the urbanized area? Two experiments are models. In the first, the residents remained on the place which was urbanized. In the second, residents were relocated in the same neighborhood and the area was recovered. At the end of the study we consider that the main cause of the problem of the occupation of the green spaces are the lack of policies that would define the destinations of these spaces, and that in cases of occupation solutions should be analyzed respecting the communities territory. Thus the ideal solution, relocation of the families and recovering of the green space, is not always the one that best serves the community.